Research on the Social Influence of Postmodernism Ideological Trend - Hu, Yanfang (Journal of Social Science and Humanities, 2024)
Postmodernism Ideological Trend opposes the wholeness and identity put forward by the western traditional philosophy and liberates people's individuality to some extent. However, with the development of postmodernism, its nature of only doubting but not constructing gradually emerges, which is difficult to guide the progress of the society and loses its original practical significance. Therefore, we should have a correct view of the post-modernism trend of thought and adhere to marxism as the guiding ideology to guide the development of China at any time.